Gamifying Reading Motivation in EFL Students: Enhancing Engagement and Language Learning Through ICT - Anggrainy, Fitri Pangestu Noer; Sharizan, Sharizan; Sriyanda, Ricky; Farhan, Muhammad (Universitas Nusantara PGRI Kediri, 2024)
This research investigates the potential of gamification in encouraging reading motivation among English as a Foreign Language (EFL) students. Reading motivation is crucial in language learning, and gamification offers promising inenues to enhance it. The study examines both reading skills and the various factors influencing reading motivation. Utilizing a conceptual paper methodology, this research systematically analyzes existing literature, theories, and concepts related to gamification and reading motivation in EFL learning, providing a comprehensive synthesis that forms the basis for understanding the potential impact of gamification on enhancing reading motivation among students. The synthesis of findings indicates that gamification positively impacts EFL learners’ reading motivation by fostering greater involvement, independence, and belief in their reading abilities. By incorporating game elements like points, badges, and leaderboards, this study reveals that through gamification in reading activities, learners not only achieve a sense of progress and competition but also overcome challenges like lack of interest, self-confidence, and autonomy in EFL reading, ultimately fostering increased motivation.